Reef building and carbonate production modes in the west-central Tethys during the Cenozoic. (May 2017) - Pomar, Luis; Baceta, Juan I.; Hallock, Pamela; Mateu-Vicens, Guillem; Basso, Daniela
Abstract: Changing components, rock textures, lithofacies, platform types and architecture throughout time are unique characteristics of carbonate rocks. Characterizing these attributes has been approached by 1) building reference models for specific Phanerozoic intervals, 2) recognizing the climatic impact in modulating carbonate production, and 3) analyzing the influence of changing bio-geochemical conditions. The reference-model approach is mostly based on biological evolution, the climatic-impact approach emphasizes temperature, and the bio-geochemical approach considers the changes in Mg/Ca ratios and Ca ++ concentrations in the oceans. To date, however, an analysis integrating all of these factors is still missing. The analysis presented here includes all these factors but also CO2, which is fundamental for both photosynthesis and CaCO3 precipitation. Here we analyze the waxing and waning of Cenozoic reef limestones from the central Tethys region through several steps: 1) on the basis of rock volume, rock textures, associated sediments and light-dependent skeletal components, as records of light penetration and wave energy (depth); 2) on global environmental conditions (δ 13 C, δ 18 O, p CO2, temperature); and 3) on the basis of functionality, nutritional requirements and available resources. Through the Cenozoic, water motion, whether induced by surface or internal waves or by currents, increased as the thermal gradients strengthened, both with depth and with latitude. Active water motion is essential for plankton catchers such as corals, but less so for many larger benthic foraminifers (LBF). Pycnoclines in the meso-oligophotic zone would then favor the benthic plankton catchers such as corals, but would be detrimental for many LBF. Warm temperatures favored LBF. The Eocene LBF families predominated during lowering of atmospheric p CO2 by using respiratory CO2 to enhance the symbiont production of photosynthates under oligotrophic conditions and limited turbulence, whereas the Miocene families had to adapt to a progressive increase in turbulence. The eurythermal coralline red algae, however, became preponderant producers in the mesophotic zone during times when the δ 13 C was relatively high. This explains two apparent paradoxes: 1) corals thrive best when the Earth's high latitudes cool, and 2) the dominance of corals and LBF is inversely correlated, despite they both require tropical conditions and have similar trophic strategies (mixotrophy). Highlights: Most Cenozoic coral buildups were small and developed in the mesophotic zone. Eocene LBF diversification and abundance coincide with warming and low p CO2 . Eurythermal red algae predominated in the mesophotic zone when δ 13 C was high. Chlorozoan sediment association developed by the Late Miocene. Before late Miocene corals thrived, along with red algae (rhodozoan), in low light conditions.